Proteomic profiling reveals oxidative phosphorylation pathway is suppressed in longissimus dorsi muscle of weaned piglets fed low-protein diet supplemented with limiting amino acids. (October 2016) - Yan, Guokai; Li, Xiuzhi; Cheng, Xiaofang; Peng, Ying; Long, Baisheng; Fan, Qiwen; Wang, Zhichang; Zheng, Zilong; Shi, Min; Yan, Xianghua
Graphical abstract: Highlights: Firstly found the piglets' OXPHOS pathway was suppressed by SLPD. Characterized the largest number of porcine skeletal muscle proteins. Found various nutrient metabolisms were affected by SLPD in piglets. Abstract: Feeding high-protein diets in animals can lead to a decrease of nitrogen utilization efficiency, and then promote the environmental pollution. Recently, more reports have demonstrated that lowering protein level in diets supplemented with specific amino acids can address these problems. However, the whole proteome alteration in the skeletal muscle of weaned piglets fed low-protein diets is poorly understood. Here, we applied the isobaric tags for relative and absolute quantification approach to investigate this alteration. We fed weaned piglets with normal protein diet (20% crude protein) and low-protein diet supplemented with lysine, methionine, threonine, and tryptophan (17% crude protein) for 25 days. Then proteomic profiling of skeletal muscles was performed. In total, 1354 proteins were quantified in the porcine skeletal muscle proteome. 132 proteins were identified as differentially expressed proteins between the two groups. Differentially expressed proteins were significantly enriched in various nutrient metabolism including lipid, carbohydrate, and amino acid metabolism. Interestingly, a total of 20 differentially expressed proteins, which are involved in the oxidative phosphorylation pathway, were all down-regulated by the low-protein diet feeding. Further immunoblotting confirmed the down-regulations of MT-ATP8, COX2, NDUFA6, and SDHB, four selected proteins among these 20 proteins. Meanwhile, the ATP level in the low-protein diet group was also reduced. These findings for the first time reveal that oxidative phosphorylation pathway is suppressed in longissimus dorsi muscle of weaned piglets fed low-protein diet supplemented with limiting amino acids, which may provide new insights into further formula design and the choice of limiting amino acids in diets.